Proteins in Microglial Activation - Inputs and Outputs by Subsets - Hanisch, Uwe-Karsten (Current Protein and Peptide Science, 2013)
Microglia serve in the surveillance, maintenance and protection of the central nervous system (CNS) homeostasis and functionality. The process of transformation from their house-keeping status to reactive phenotypes upon CNS challenges is known as microglial activation. It comes also with dramatic changes in protein expression and release. Activated microglia may thereby mount a rather homogenous response, with all cells of an affected local population simultaneously upregulating the same cell surface receptors or synthesizing an identical set of soluble messengers. Yet there is increasing evidence for a constitutive heterogeneity of microglia by and within CNS regions—largely being based on protein expression as well as activities and pointing to distinct functional capacities as to microglial subtypes. Inductions of proteins with key functions in antigen presentation and inflammation, like major histocompatibility complex (MHC) class I or II molecules and tumor necrosis factor (TNF) α, reveal that among a pool of activated microglia individual cells can differ by actual contributions. While MHC I induction can be appropriately triggered as a panpopulational response, only a subset would organize for TNFα production. Similarly, MHC II expression seems to be confined to a microglial subpopulation, and disposal of myelin either under normal conditions or its removal upon CNS damage appear to be duties of specialized cells, partially with complementary distribution. Discrete synthesis of immunoregulatory proteins would thus assign a master control to certain microglia, while tasks in the clearance of endogenous material and in professional antigen presentation could be sequestered to avoid collision of incompatible functions.
Keywords: DAMP